Bioseguridad: conocimientos, actitudes y prácticas en estudiantes de las carreras de Bioquímica y Veterinaria de la Universidad Católica de Córdoba. - Irrazabal, M.G. (2019)
Biosecurity is an issue of fundamental importance during training and professional practices in many careers. This is due it?s consequences, that may impact both on people?s and the environment health. This research aimed to clarify the level of knowledge, attitudes and the way to proceed of the students. A descriptive cross-sectional study was carried out on 266 university students of Veterinary and Biochemistry, of the Universidad Católica de Córdoba. Data were collected by means of a structured questionnaire.\nMore than 80% of the students were aware of the risks that they may deal with during the exercise of their profession, as infectious and contagious diseases. However, during the year most of them did not stick to the theory, incurring in unsafe practices as smoking or drinking during laboratory practices. Biosecurity must be a priority issue within the careers of Veterinary and Biochemistry, along with the professor?s well-known responsibility of setting the example in secure laboratory procedures.